Use of blogs to improve the english writing skill, in eighth grade students classroom "C" at Military High School Nº 13 Patria during the first quimestre, school year 2015-2016 - Bonilla Lechón, Néstor Benjamín (2016)
Science and technology have rapidly advanced in the 21st century and important programmers around the world have developed different software to meet the interests and needs of users. (Mora Ana , 2009) That is why the academic field and specifically English learning in Ecuador has sought new technological tools that are useful for the development of key skills (such as listening, speaking, reading and writing) thus making a more effective method of teaching- learning English . One of the technological tools currently more used in the academic field are blogs, tool that was used to improve the English writing skill in eighth grade students at Military High School Nº 13 "Patria". Important tools have been added to the blogs in order to allow the constant and interactive communication between the teachers and students, there will also be feedback after each activity to correct errors. Each student can observe the participation of their partners that serve as a basis to correct an error at once. Weekly online and written evaluations will take place in the classroom after finishing a particular subject of study; this allows checking the progress of the students